On Functional Purpose of Legal Liability - Vladimir Valentinovich Kozhevnikov (SIASAT, 2021)
The general theoretical and sectoral aspects of the problem of the functions of legal responsibility are considered. The author proceeds from the fact that the main methodological mistake of supporters of the restorative function of legal responsibility is that they often identify measures of legal responsibility and protection measures.